2002
DOI: 10.1053/bbmt.2002.v8.pm12374454
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous versus oral busulfan as part of a busulfan/cyclophosphamide preparative regimen for allogeneic hematopoietic stem cell transplantation: Decreased incidence of hepatic venoocclusive disease (HVOD), HVOD-related mortality, and overall 100-day mortality

Abstract: Hepatic venoocclusive disease (HVOD) is a complication of allogeneic hematopoietic stem cell transplantation (HSCT) and is a well-recognized dose-limiting toxicity of oral busulfan (Bu)-based preparative regimens. The unpredictable absorption of oral Bu from the gastrointestinal (GI) tract and hepatic first-pass effects have led to the development of an intravenous Bu preparation (i.v. Bu). The purpose of this retrospective comparison was to evaluate the incidence rate of HVOD and the 100-day mortality rate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
149
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(158 citation statements)
references
References 13 publications
4
149
2
3
Order By: Relevance
“…BU showed satisfactory dose assurance with reliable predictability of pharmacokinetics without dose adjustment. 19 Hence, it is very probable that its use reduces the incidence of various risks at transplantation such as hepatic venoocclusive disease (VOD), as shown by Kashyap et al 21 Nevertheless, drug profiles of i.v. BU preparation have not been fully evaluated in different races, who may have different pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…BU showed satisfactory dose assurance with reliable predictability of pharmacokinetics without dose adjustment. 19 Hence, it is very probable that its use reduces the incidence of various risks at transplantation such as hepatic venoocclusive disease (VOD), as shown by Kashyap et al 21 Nevertheless, drug profiles of i.v. BU preparation have not been fully evaluated in different races, who may have different pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is unsurprising given that the other conditioning regimens, involving radiotherapy and/or chemotherapy, are associated with more pronounced toxicities and side effects. 15,16 Interestingly, we also found that the symptom of fever and the proportion of BM primitive cells were significant predictors of disease-free and overall survival. These are surprising findings that are difficult to explain.…”
Section: Discussionmentioning
confidence: 56%
“…In addition, high BU levels are documented to cause acute chemical hepatitis by depleting glutathione in hepatocytes, and, probably, predisposing to VOD. 17 Hence, i.v. BU was developed to counter the first pass effect of oral leading to much less variability in the pharmacokinetic profile and a decrease in the incidence and severity of VOD.…”
Section: Discussionmentioning
confidence: 95%
“…(0.8 mg/kg) BU is comparable to oral (1 mg/kg) BU dosage. 17 However, Slattery 24 noted in response that the comparison had failed to account for the differences in BU area under the plasma concentration time curve. The mean area under the curve (AUC) for i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation